Low-Level Laser Effect on Post-exodontia Inflammation of the Lower Third Molar (Revista Nacional de Odontología, 2017)
Introduction: The use of Low-level Laser Therapy (Low-level Laser Therapy, lllt ) has brought with it theevolution of anti-inflammatory, analgesic and pro-healing treatments due to cell photostimulation onthe mitochondria; this increases the generation of energy (atp), which accelerates blood microcircula-tion and produces changes in the hydrostatic pressure of the capillary. Case presentation: A 25-year-old patient who attended the oral surgery service at the dental clinics ofa university for the extraction of retained lower third molars. Upon radiographic examination, asympto-matic tooth 48 was observed in mesioangular position according to Winter’s classification and classb ii according to Pell & Gregory’s classification. Materials and methods: The patient received post-exodontia treatment with Low-level Laser Therapy. Results: The effect achieved with the application of lllt in the case resulted in pain control at 48 hours,anti-inflammatory effect on the third day and evident tissue regeneration on the seventh day. Conclusions: Low-level Laser Therapy could be an alternative post-surgical control of retained thirdmolar extractions that would prevent the administration of anti-inflammatory and analgesic drugs insome cases.
Keywords: wound healing; regeneration; laser therapy; third molar; trismus (DeCS)